Effect of calfhood nutrition on metabolic hormones, gonadotropins, and estradiol concentrations and on reproductive organ development in beef heifer calves. (21st September 2020) - Kelly, Alan K; Byrne, Colin; McGee, Mark; Perry, George A; Crowe, Mark A; Sauerwein, Helga; Kenny, David A
Abstract: This study examined the effect of plane of nutrition on the endocrinological regulation of the hypothalamic–pituitary–ovarian (HPO ) axis in beef heifer calves during a critical sexual developmental window early in calf hood. Forty Holstein-Friesian × Angus heifers (mean age 19 d, SEM = 0.63) were assigned to a high (HI ; ADG 1.2 kg) or moderate (MOD ; ADG 0.50 kg) nutritional level from 3 to 21 wk of life. Intake was recorded using an electronic calf feeding system, BW was recorded weekly, and blood samples were collected on the week of age 5, 10, 15, and 20 for metabolite, reproductive, and metabolic hormone determination. At 19 wk of age, on sequential days, an 8-h window bleed was carried out for luteinizing hormone (LH ), follicle-stimulating hormone (FSH ), and estradiol analysis. To characterize anterior pituitary gland function, an intravenous GnRH challenge was conducted (19 wk of age). Blood was collected via a jugular catheter every 15 min for 135 min for the analysis of LH, FSH, and estradiol. Calves were subsequently euthanized at 21 wk of age; the anterior pituitary, metabolic organs, and reproductive tract were weighed, and ovarian surface follicular numbers and oocytes recovered were recorded. Mean ADG was 1.18 and 0.50 kg for HI and MOD, respectively, resulting in a 76.6-kg difference in BW ( P < 0.001). Blood insulin, glucose, and IGF-1 concentrations were greater ( P < 0.001) for HI compared with MOD. There was a diet × time interaction for leptin ( P < 0.01); concentrations were greater in HI compared with MOD at 20 wk of age with no difference between treatments before this. Dietary treatment did not alter the concentrations of adiponectin or anti-mullerian hormone. There was a diet × time interaction for FSH, whereby MOD had greater concentrations than HI at 10, 15, and 20, but not at 5 wk of age. Over the duration of an 8-h window bleed (19 wk of age), serum concentrations of LH, LH pulse frequency, and LH pulse amplitude were unaffected by treatment, whereas FSH (0.23 vs. 0.43 ng/mL) and estradiol (0.53 vs. 0.38 ng/mL) concentrations were less than and greater, respectively, for HI than MOD ( P < 0.05). Likewise, following a GnRH challenge, the area under the curve analysis revealed greater ( P < 0.01) estradiol and lesser ( P < 0.01) FSH concentrations in calves on the HI relative to MOD diet, whereas concentrations of LH were unaffected ( P = 0.26) between treatments. Ovarian surface follicle numbers were greater ( P < 0.05) in HI compared with MOD. Total reproductive tract, uterus, and ovarian tissue expressed relative to BW were greater ( P < 0.05) for HI compared with MOD. In conclusion, enhanced nutrition in early calfhood advances the ontogeny development of the HPO axis.